Optimisation of biomass-fired cogeneration plants using ORC technology. (October 2020) - Świerzewski, Mateusz; Kalina, Jacek
Abstract: In this paper, the problem of optimal sizing of biomass-fired ORC combined heat and power (CHP) unit for existing coal-fired district heating (DH) plant is discussed. The study examines the influence of boundary conditions on the optimal design characteristics of the ORC CHP system within heating plant backfitting project. The optimisation task is solved for given site-specific technical, economic, ecological and legal constraints. The proposed methodology for synthesis of new technological structure takes into account long-term operational experience and results of measurements of a given reference plant. Although the methodology is general, the solution presented in the paper is relevant for Polish DH sector. The analysis considers country specific system of financial incentives for renewable energy projects as well as participation in electricity balancing market and European Trading System (ETS). Thermal energy storage is considered as a solution providing flexibility of CHP system operation. Influence of different electricity, biomass, coal and EUA (European Emission Allowance) prices on optimal size and structure of the cogeneration system is examined. The analysis revealed that economic optima are relatively flat and the range of ORC unit size, for which the value of objective function is close to the optimum is quite wide. Although Net Present Value (NPV) and Internal Rate of Return (IRR) suggest slightly different size of the system, the recommended solutions are the ones with relatively long annual time of operation. The optimum size of ORC for a DH system of approximately 30 MW peak heating output is within the range of electric power of 1–2 MW. It was also found that although market prices and support instruments are nowadays different than at the time of commissioning of the reference plant, the size of the ORC unit is still close to the optimal value. Implementation of thermal energy storage (TES) in the form of hot water storage tank moves the optimal rated electric power of the ORC generator slightly towards higher values. On the other hand, only a small improvement of financial performance is gained by implementation of TES. Considerable improvement of economic performance has been reached after anticipated increase paths for electricity and EUA prices were introduced. In this case however, the recommended optimal size of the ORC CHP remained almost the same as in the case of constant prices. Highlights: Optimal sizing of biomass-fired ORC CHP unit for district heating plant is presented. Alternative methodology based on measurement data from existing reference plant is proposed. Participation in electricity balancing market and European Trading System (ETS) is considered. Location of optimum is mostly determined by system technical performance. Optimally sized ORC CHP unit should cover base heating load of district heating grid.